Simultaneous Determination of Paracetamol, Domperidone and Flunarizine in Combined Tablet Dosage Form Using RP-HPLC Method - Dubey, Nitin; Khan, Naziya; K. Jain, Dinesh (Asian Journal of Chemistry, 2012)
A simple, selective, accurate high performance liquid chromatographic (HPLC) method have been developed and validated for the analysis of paracetamol, domperidone and flunarizine. Chromatographic separation was achieved on Luna C8 column using mobile phase of methanol:acetonitrile:phosphate buffer (55:30:15, % v/v/v, pH 7.0) at a flow rate of 1.0 mL/min with UV detection at lmax of 249, 284 and 254 nm for paracetamol, domperidone and flunarizine, respectively. The retention time of paracetamol, domperidone and flunarizine was found to be 2.95, 4.05 and 10.3 min, respectively. The method was validated as per ICH guidelines. The method may be applied for the routine simultaneous estimation of the above mentioned drugs in tablet dosage form.